PERFORMANCE OF MUSICAL MODES FROM MAQAM SECTORS - Mukhsimjon Mansurovich Muminov, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  The  article  provides  recommendations  on  breathing  control, performance  technique,  visual  expression  techniques,  and  practice  in  developing students' voices. The processes of performing maqom sections in ensemble and solo performance,  ensuring  musical  harmony,  and  monitoring  performance  skills  are highlighted; the international significance of maqom art and the role of students in conveying it to the younger generation are emphasized.